Efektifitas Program Pilah Sampah dari Rumah (Pilsadar) berdasarkan Peraturan Daerah Kota Mataram Nomor 1 Tahun 2019 tentang Pengelolaan Sampah - Lanang Sakti; Asmi Adwiasa Perdana; Muhammad Rosikhu (Juridische : Jurnal Penelitian Hukum, 2024)
This research aims to examine the effectiveness of the Home Waste Sorting Program (PILSADAR) in Tanjung Karang Village, Sekarbela District, Mataram City Based on Mataram City Regional Regulation Number 1 of 2019 concerning Waste Management. This thesis examines the following problems, namely; What is the effectiveness of the Home Waste Sorting Program (Pilsadar) in Tanjng Karang Village, Sekarbela District, Mataram City; and what are the obstacles faced in implementing the Home Waste Sorting Program (Pilsadar) in Tanjung Karang Village, Sekarbela District, Mataram City. This research is research that examines data and legal materials, both from primary data obtained from field observations and interviews, and from secondary data consisting of primary legal materials in the form of statutory regulations and other regulations. related. From the results of this research, it can be concluded that; Sapaia's PILSADAR program is currently not running effectively because this program has only been implemented in the Sembalun area and is only implemented twice a week. The author says that there needs to be more intensive evaluation and coordination as well as follow-up to ensure that PILSADAR is implemented according to expectations and achieves appropriate results. Overall, this could have a positive impact on the entire Tanjung Karang Village; Furthermore, the obstacles faced by the Government in implementing the Segregate Waste from Home (Pilsadar) Program in Tanjung Karang Subdistrict are the limited budget in the subdistrict which is the main obstacle in implementing the pilsadar program. This shows that limited financial resources can limit the expansion of the program to other areas. Apart from that, the lack of limited three-wheeled vehicles is also an inhibiting factor. This can hinder the distribution of rubbish sacks or transport of rubbish from home to waste management centers.